The impact of Drama Therapy on Improving Pragmatic Language Skills among children in the kindergarten stage in Jeddah (The International Journal of Educational Sciences and Arts, 2026)
The present study aimed to investigate the effectiveness of a program based on drama therapy in improving pragmatic language skills among children in the kindergarten stage in the city of Jeddah. The study was conducted on a sample of 40 kindergarten students aged between 4 and 5 years, with a mean age of 4.6 years and a standard deviation of 0.89. The participants were equally divided into an experimental group and a control group. The sample was equally divided into an experimental group and a control group. The quasi-experimental approach was adopted to implement the study procedures. The instruments used included the Pragmatic Language Scale (developed by the researcher) and the drama therapy-based program (developed by the researcher). The results revealed the effectiveness of the program, as statistically significant differences were found between the mean ranks of the experimental group's scores on the Pragmatic Language Scale in the pre-test and post-test in favor of the post-test. Statistically significant differences were also found between the mean ranks of the experimental and control groups in favor of the experimental group. Furthermore, no statistically significant differences were observed between the mean ranks of the experimental group's scores in the post-test and follow-up test. The researcher recommended utilizing drama therapy to enhance pragmatic language skills among children in the kindergarten stage.
Keywords: Drama Therapy; Pragmatic Language; kindergarten Children; Jeddah